Retrospective study of the situation of Brazilian countryside schools and conceptions of teachers of rural public schools in the municipality of Itapuranga, Goiás, Brazil - Letícia de Sousa Silva; Jonathas Rodrigues Siqueira Costa; Liliane de Sousa Silva; Carla Rosane Mendanha da Cunha (Universidade Federal do Norte do Tocantins, 2020)
The aim of this study was to understand the underlying context of the countryside education according to the teachers in the municipality of Itapuranga-GO, as well as retrospective analysis of the closure of the countryside schools and the number of enrollments. Data collection included application of a questionnaire about teachers' conceptions and concepts regarding the structure, transportation, professional training and transformations in education in the school of the countryside in which they work. The survey with the teachers was carried out in August 2017 and the search for the number of enrollments and schools was carried out on the databases of QEdu and IBGE (Brazilian Institute of Geography and Statistics). Municipality of Itapuranga has two rural municipal schools, the Betel Municipal School and Serra Dourada Municipal School, containing 08 and 03 teachers, respectively. Only 09 teachers agreed to participate in this study, being 5 of the female and 4 of the male gender. The age of teachers varied from 30 to 50 years. They all have degrees in areas such as Pedagogy, Letters (English), Mathematics and/or History, and only has a complementary course in the field of countryside school, which is in Family Farming. It was verified that the management model, the contents, the projects and the training of teachers of the countryside schools of the municipality follow the same Pedagogical Political Project (PPP) of the urban schools and that there is not an effort of the state and the professionals to adapt the rural schools within established principles.